2016
DOI: 10.5334/jbr-btr.1209
|View full text |Cite
|
Sign up to set email alerts
|

Optimising TNM Staging of Patients with Prostate Cancer Using WB-MRI

Abstract: Multiparametric Magnetic Resonance Imaging (mp-MRI) is the current standard of reference for the local staging of prostate cancer (PCa). On the other hand, despite the low sensitivity and specificity of Technetium Bone Scanning (BS) for the detection of bone metastases (BM) and of Body Computed Tomography CT for the detection of lymph node metastases (LNM), these techniques are routinely used, in the current clinical practice. Nevertheless, whole Body MRI (WB-MRI) and Positron Emission Tomography Computed Tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The detectability of bone and lymph node metastasis with whole‐body MRI is superior to that with CT, and whole‐body MRI can be an alternative modality to BS and CT in staging diagnosis . Whole‐body MRI has several merits that include the ability to perform repeated tests over time, cost‐effectiveness in our country, no radiation exposure, no use of contrast material, and comprehensiveness with one examination for bone, other organs, and lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detectability of bone and lymph node metastasis with whole‐body MRI is superior to that with CT, and whole‐body MRI can be an alternative modality to BS and CT in staging diagnosis . Whole‐body MRI has several merits that include the ability to perform repeated tests over time, cost‐effectiveness in our country, no radiation exposure, no use of contrast material, and comprehensiveness with one examination for bone, other organs, and lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of DWIBS is the strong contrast of positive signals against normal tissues; thus, DWIBS is useful for identifying primary and metastatic lesions. DWIBS can also detect osteolytic changes, lymph node metastasis, and visceral metastasis in addition to osteoblastic changes . We encountered cases of CRPC wherein we could not detect osteolytic bone metastasis in the sacrum with CT (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown higher sensitivity of WB-MRI compared to 18FDG-PET-CT for the detection of both focal and diffuse bone involvement. 105 WB-MRI is now being developed for routine clinical use in prostate cancer 106 . In a study assessing the diagnostic accuracy of WB-MRI in newly diagnosed intermediate-risk and highrisk disease 20 , the mean sensitivity and specificity for N1 disease were 1.00 and 0.96, respectively, whereas for M1b disease, the mean sensitivity and specificity were 0.90 and 0.88, respectively.…”
Section: [H1]wb-mri and Its Changing Landscape In Prostate Cancermentioning
confidence: 99%
“…She obtained her MD from the University of Ioannina, Greece, and following that she worked as a radiology resident at Université de Liège . After three years, she arrived at Université Catholique de Louvain in Brussels to commence her PhD thesis titled ‘’One step TNM staging of patients with high risk prostate cancer using MRI” [ 5 ]. Dr. Pasoglou was awarded the prestigious ESUI Vision Award 2015 for her work ‘’Whole-body 3D T1-weighted MR imaging in patients with prostate cancer: feasibility and evaluation in screening for metastatic disease’’.…”
mentioning
confidence: 99%